Genetic diversity and phylogenetic analysis of Crimean-Congo Hemorrhagic Fever viruses circulating in Pakistan during 2019. - Massab Umair; Adnan Khurshid; Muhammad Masroor Alam; Ribqa Akhtar; Muhammad Salman; Aamer Ikram (Public Library of Science (PLoS), 2020)
Being an endemic country for Crimean Congo hemorrhagic fever (CCHF), this study aimed to explore the genetic diversity of CCHF virus (CCHFV) detected in Pakistan during 2019. Serum samples from patients with clinical signs of hemorrhagic fever attending tertiary care hospitals in Pakistan were tested for CCHFV RNA using real-time PCR at Department of Virology, National Institute of Health. The partial S-gene fragments were directly sequenced to determine the prevailing CCHFV genotypes and their molecular epidemiology in Pakistan. During January-December 2019, 280 samples from suspected CCHF patients were tested and 28 (10%) were found positive on real-time PCR. Positive cases were detected from 14 districts and across all four provinces of Pakistan with majority reported during August-September. The mean age of CCHFV positive patients was 37.25 years (range 5-65 years) with a high frequency in males (92.8%; n = 26) and a case fatality rate of 40.7% was observed. Phylogenetic analysis showed that S- segment of 2019 PAK CCHFV strains (n = 13) belonged to Asia-1 genotype and clustered with regional strains from Iran, Oman, and Afghanistan. We conclude that Asia-1 genotype of CCHF virus remains endemic in Pakistan. Our findings emphasize to establish a laboratory based surveillance program to monitor the disease burden and identify outbreak hotspots for effective control.